Didactic Foundations and Pedagogical Potential of Flipped Classroom Methodology in TESOL - Sultonova, Marvarid Abdulvohid qizi (The Lingua Spectrum, 2026)
This study investigates the didactic foundations and pedagogical potential of the flipped classroom methodology in Teaching English to Speakers of Other Languages (TESOL). The research is grounded in contemporary educational frameworks, including constructivist learning theory, communicative language teaching, and competency-based education. Particular emphasis is placed on fostering learner autonomy, promoting interactive engagement, and enhancing communicative competence within higher education environments. Rather than interpreting flipped learning as a purely technological innovation, the study conceptualizes it as a systematic transformation of instructional design that redefines the distribution of cognitive and pedagogical processes. The analysis incorporates psychological, methodological, and institutional dimensions, emphasizing their interconnected role in effective implementation. Based on preliminary observations, the structured application of flipped instruction increases student participation, strengthens self-regulated learning strategies, and improves communicative performance. In the context of Uzbekistan’s higher education system, this approach demonstrates significant potential for modernizing TESOL practices and aligning them with international academic standards and contemporary pedagogical expectations.